2020
DOI: 10.1097/shk.0000000000001696
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectroscopy Derived Tissue Hemoglobin Oxygen Saturation in Critically Ill and Injured Patients

Abstract: Background: In this study, we examined the ability of resonance Raman spectroscopy to measure tissue hemoglobin oxygenation (R-StO 2 ) noninvasively in critically ill patients and compared its performance with conventional central venous hemoglobin oxygen saturation (ScvO 2 ). Methods: Critically ill patients (n ¼ 138) with an indwelling central venous or pulmonary artery catheter in place were consented and recruited. R-StO 2 measurements were obtained by placing a sensor inside the mouth on the buccal mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Studies in adults found that changes in perfusion and oxygenation in the oral mucosa and gastrointestinal tract reflect whole-body oxygenation [18,19]. In the first arm of the study, we found that the buccal mucosa and the thenar eminence are equally suitable sites for the measurement of RRS, supporting previous studies showing good correlation of buccal/sublingual and skin RRS-StO2 with S CV O 2 in animal models [12,13] and in humans [14]. Because the thenar eminence is relatively devoid of any pigment, it is likely an optimal site for analysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Studies in adults found that changes in perfusion and oxygenation in the oral mucosa and gastrointestinal tract reflect whole-body oxygenation [18,19]. In the first arm of the study, we found that the buccal mucosa and the thenar eminence are equally suitable sites for the measurement of RRS, supporting previous studies showing good correlation of buccal/sublingual and skin RRS-StO2 with S CV O 2 in animal models [12,13] and in humans [14]. Because the thenar eminence is relatively devoid of any pigment, it is likely an optimal site for analysis.…”
Section: Discussionsupporting
confidence: 87%
“…The splanchnic saturation of RRS-StO2 and NIRS measured simultaneously in a hemorrhagic pig model shows that RRS-StO2 is an earlier predictor of tissue dysoxia compared to NIRS [13]. Recently, RRS applied in adults showed a good correlation of RRS-StO2 measured in the buccal mucosa against S CV O 2 [14]. A similar study carried out in newborns to correlate S CV O 2 with RRS-StO2 in the lower extremity did not find a correlation [15].…”
Section: Introductionmentioning
confidence: 86%
“…The study reported a Clarke Error Grid where 84.8% of the data was within the accurate and acceptable grids. The clinical utility yielded an agreement of 0.45 [ 64 ]. The other study evaluated the agreement between commercial electronic thermometers against a gold-standard arterial thermometer in estimating the body temperature of patients in critical care (see Table S4 of the Supplementary Material ).…”
Section: Resultsmentioning
confidence: 99%
“…We continue our theme of resuscitation as Tiba et al invite readers to consider a new perspective on tissue perfusion (5). These authors emphasize the importance of surrogate markers for tissue oxygenation in the management of the critically ill patient.…”
mentioning
confidence: 94%